Osobowy wymiar małżeństwa kanonicznego jako punkt odniesienia w pracy biegłego psychologa - Stepulak, Marian Zdzisław (Ius Matrimoniale, 2003)
One of great dangers in the work of a psychologist working as an advisor to the church tribunal is a situation, when he forgets about the need for personal understanding of his client - one of the parties in the trial. The psychologist advisor working in a bishop’s court must also work out for himself a new view on the entity of marriage as a sacrament. For that view will allow him discover the personal dimension of a catholic marriage. Is is also the duty of a psychologist advisor, fulfilling his mission in the church tribunal to learn the basics of the modern doctrine and law of the Catholic Church towards the personal relationship of two people that marriage is.